2007
DOI: 10.1590/s1676-06032007000100027
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary data on the feeding habits of the freshwater stingrays Potamotrygon falkneri and Potamotrygon motoro (Potamotrygonidae) from the Upper Paraná River basin, Brazil

Abstract: Stingrays of the Potamotrygonidae family are a singular group of Neotropical ichthyofauna. Although ancient reports exist about the group, there are still many questions that need to be clarified, such as the biology of the species that occur in the Paraná-Paraguay River system. In the present work, the diet of Potamotrygon falkneri and Potamotrygon motoro, captured in the Upper Paraná River, downstream from the Engenheiro Souza Dias Hydroelectric Power Station (UHE Jupiá), was analyzed. Both species showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 11 publications
0
24
0
2
Order By: Relevance
“…Ontogenetic differences in dietary habits and between immature and mature individuals have been reported for freshwater stingrays by Charvet- Almeida (2006) and Silva and Uieda (2007), as well as for marine batoids (Muto et al, 2001;Moura et al, 2008).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Ontogenetic differences in dietary habits and between immature and mature individuals have been reported for freshwater stingrays by Charvet- Almeida (2006) and Silva and Uieda (2007), as well as for marine batoids (Muto et al, 2001;Moura et al, 2008).…”
Section: Discussionmentioning
confidence: 81%
“…An essentially insectivorous diet was also reported for the congeners P. orbignyi (Lasso et al, 1996;Rincon, The numbers in bold correspond to the highest values. 2006; Charvet- Almeida, 2006) and P. motoro from the upper Paraná River (Silva and Uieda, 2007). On the Marajó Island, at the lower Amazon drainage, P. motoro also consumed insects, but decapod crustaceans and fish were the dominant items .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potamotrygonidae stingrays consume a wide variety of prey, feeding on insects, mollusks, crustaceans, and teleosteans (Lasso et al 1996, Lonardoni et al 2006, Rincon-Filho 2006, Silva & Uieda 2007, Shibuya et al 2009). Their diets may be directly related to the availability of any given prey, and some species display specific dietary habits [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Specimens of Potamotrygon motoro (Müller & Henle 1841) from the Middle Negro River in the Brazilian Amazon is known to consume principally crustaceans, although teleosteans also appear to be an important element in its diet (Lasso et al 1996, Shibuya et al 2009). Silva & Uieda (2007) reported that the two potamotrygonid species found in the Paraná River (Potamotrygon falkneri Castex & Maciel 1963 and P. motoro) have diversified diets, and teleosteans were found in the stomach contents of just one specimen of each species. In addition to these observations, Garrone-Neto & Uieda (2009) pointed out that the rare occurrences of catfishes (Siluriformes) in stingray diets may be considered occasional, as a consequence of inexperience and/or an accidental predation, since one of the analyzed specimens (a young individual of P. falkneri) had a dead catfish stuck in its oral chamber.…”
Section: Introductionmentioning
confidence: 99%